Makna Prasa “Biarkanlah Anak-anak itu Datang Kepada-Ku dan Janganlah Kamu Menghalang-halangi Mereka” dalam Lukas 18:16 dan Implikasinya Bagi Gereja Masa Kini - Yuliono Evendi; Agustina Ace Wagena (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
The statement of Jesus in Luke 18:16, “Let the little children come to Me, and do not hinder them,” contains a theological message that remains relevant for the church throughout the ages. This study aims to examine the meaning of this phrase through a biblical exegesis approach, considering the historical, grammatical, and theological context of the Gospel of Luke. The research employs a qualitative method with historical-grammatical hermeneutics and a literature review on children’s ministry from a New Testament perspective. The findings indicate that the phrase emphasizes Jesus’ indiscriminate acceptance of children as full members of the faith community while rejecting any structural, cultural, or spiritual barriers that diminish the value and rights of children in congregational life. The implication for the contemporary church is the need to develop an inclusive, holistic, and child-friendly ministry in liturgy, education, and spiritual formation, as well as to remove obstacles that may hinder the spiritual growth of children. Thus, the message of Luke 18:16 provides a strong theological foundation for building a church that honors and empowers children as heirs of the Kingdom of God.